Evaluation of cellular safety and the chemical composition of the peanut (Arachis hypogaea L.) ethanolic extracts - Menis Candela, Florencia (2020)
Arachis hypogaea L. (Leguminosae) is distributed in tropical and subtropical areas. Peanut has high nutritional and commercial value. Scientific research showed that peanut has biological properties such as anticancer, antioxidant, antiinflammatory. However, it is necessary to know if consumption of peanut, either as food or as a phytopharmaceutical implies a health risk. The aim was to evaluate cytotoxicity and genotoxicity of ethanolic extracts from A. hypogaea. Also, chemical characterization of these extracts was performed. Cytotoxicity was evaluated by MTT and Neutral Red Uptake (NRU) assays on Vero cells. Genotoxicity was studied by Micronuclei and comet assays on Balb/C mice. Qualitative and quantitative chemical analysis of extracts were performed. Results showed that extracts have low cytotoxicity. Tegument ethanolic extract (TEE) and Seed ethanolic extract (SEE) were not genotoxic. The treatments with TEE at 250 mg/kg and SEE at 2000 mg/kg revealed (highest concentrations evaluated) some toxicity on blood marrow cells of mice. Chemical characterization indicated that TEE had 74.33 1.10 mg GAE/g of dried extract and SEE had 15.05 0.06 mg GAE/g of dried extract of total phenolic content. Also, proanthocyanidins (O.D. at 550 nm 1.39 0.15) and caffeic acid (2.46%) were identified in TEE. While, linoleic acid (58.84%) oleic acid (11.31%) and palmitic acid (8.37%) were major compounds of SEE. In conclusion, peanut consumption is safe at concentrations recommended for healthy uses, such as nutrition, and phytomedicine.